THE 450 YEARS OLD PSALMS FROM GENEVA AND THE ATTEMPT TO TRANSLATE THEM INTO ROMANIAN - Csaba PÉTER (Studia Universitatis Babeş-Bolyai. Musica)
In the midst of the written records of protestant missions held among the Transylvanian Romanians we put a great store on translating the congregational songs, mainly the psalms from Geneva to Romanian. With this effort they tried to take the common people into the cultic acts with the use of active and understandable language, in an acceptable form.